Reinforced concrete building design project & project based learning (Case Study) / Irr Razuan Imran - Imran, Irr Razuan (2022)
As a conclusion, the flexible pavement is commonly be used al around the world because of the initial cost which is not expensive compare to the rigid pavement. The cost might be low but the maintenance should be regularly. For this road, to design the flexible pavement is enough because of the usage vehicle is not really high. The grade of the bitumen that use for the pavement have to choose the perfect grade according to the country weather. As in Malaysia, we can provide the bitumen grade of 60 / 70. It is because Malaysia has high temperature which the bitumen grade can adapt to the weather in term of the softening point.